Ketuhanan Dalam Puisi-puisi Abizai Dari Perspektif Teori Takmilah - Yan, Helmi (2022)
Abizai (Zainal Abidin Hj Suhaili) is a Sarawakian writer who is associated with Islamic poetry writing. Abizai often expresses spiritual theme and arty language in his works. This study intends to explore divinity aspects, identify preaching elements, and analyse the aesthetics in his poems. Research methodology that is used here is content analysis. Seven poem collections that were studied are Seekor Kelawar di Kamar Pengantin, Mengenal yang Asal, Membentuk Elok di Teluk Esok, Sang Kelawar Kesiangan, Sinar Benar, Merdeka Burung and Kitab Rahsia. Takmilah theory that was proposed by Shafie Abu Bakar is adopted to analyse the poem collections. The principles in Takmilah theory that were chosen for this study are the principle that Divine is kamal (perfect), the principle that the audience are edified to be insan kamil (perfect beings) and the principle that literature is aesthetic and takmilah (complete and complementary). Findings show the principle that Divine is kamal, through the use of divinity theme is clearly shown as repository of oneness in Abizai's poems. Piety and obedience become the way of encouraging the audience to have faith in the existence of Allah SWT through His creation. Based on the principle that edified the audience to be insan kamil, describing the poet personality as someone that is prone towards divine and spiritual theme made Abizai's works as a medium to preach and nurture insan kamil in terms of moral and implementation of Islamic law.